Migration Analysis of Physicians Practicing in Hawai‘i from 2009–2011 - Stephens, Laura D (University Clinical, Education & Research Associate (UCERA), 2012)
BACKGROUND: Hawai‘i suffers a 20% shortage of physicians. Examining physician migration patterns into and out of Hawai‘i may better inform physician recruitment and retention techniques. METHODS: 2009–2011 practice location data on all non-military, practicing physicians in Hawai‘i were compiled in a database maintained by the University of Hawai‘i John A Burns School of Medicine, Area Health Education Center (AHEC). Medical school attended was extracted from an AMA Masterfile list. Physicians were contacted or searched online to ascertain practice location as of September 2011. RESULTS: Currently 3,187 physicians actively practice in Hawai‘i; 2,707 (84.9%) trained at a total of 136 US medical schools. Nearly half of all US-trained physicians attended medical school in Hawai‘i, California, New York, Illinois, or Pennsylvania. International medical graduates represented 191 medical schools from 67 distinct countries, primarily in the Philippines (23.1%). From 2009–2011, 238 physicians retired from clinical activity, and 329 physicians left Hawai‘i to practice in other locations. California received the largest portion of Hawai‘i's former physicians (26.4%). Only 15.5% of physicians returned to the state where they attended medical school. DISCUSSION: Medical schools with some of the most alumni practicing in Hawai‘i (eg, Creighton, UCLA, Georgetown) all have active Hawai‘i student clubs, suggesting a target for recruitment efforts. Physician emigration cannot be fully explained by geography of a physician's medical school alma mater. Analysis of physician residency locations and exit surveys of physicians leaving Hawai‘i are recommended for future study.